2020
DOI: 10.1111/ene.14201
|View full text |Cite
|
Sign up to set email alerts
|

EAN/ERS/ESO/ESRS statement on the impact of sleep disorders on risk and outcome of stroke

Abstract: Background: Sleep disorders are highly prevalent in the general population and may be linked in a bidirectional fashion to stroke, which is one of the leading causes of morbidity and mortality. Aim: Four major scientific societies established a task force of experts in neurology, stroke, respiratory medicine, sleep medicine and methodology to critically evaluate the evidence regarding potential links and the impact of therapy. Materials and methods: Thirteen research questions were evaluated in a systematic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 162 publications
(350 reference statements)
2
66
1
10
Order By: Relevance
“…In a systematic review of stroke and TIA patients, 10 studies all reported that BSD increased vascular events or mortality [ 52 ]. BSDs might improve with stroke recovery but elevated mortality continuously after the acute stage [ 53 , 54 ].…”
Section: Breathing-related Sleep Disorders (Bsds) and Strokementioning
confidence: 99%
“…In a systematic review of stroke and TIA patients, 10 studies all reported that BSD increased vascular events or mortality [ 52 ]. BSDs might improve with stroke recovery but elevated mortality continuously after the acute stage [ 53 , 54 ].…”
Section: Breathing-related Sleep Disorders (Bsds) and Strokementioning
confidence: 99%
“…
6,10 on behalf of the SAS-CARE study group ABSTRACT Sleep-disordered breathing (SDB) is frequent in patients with acute stroke. Little is known, however about the evolution of SDB after stroke.
…”
mentioning
confidence: 99%
“…A recent statement of the European Neurology, Pulmonology, Sleep, and Stroke Societies [ 19 ] has come to a similar conclusion, while emphasizing the existence of a bidirectional relationship between sleep and stroke and stressing the need for further mechanistic and therapeutic investigations.…”
Section: Introductionmentioning
confidence: 87%